Effectiveness of Structured Mentor Training on Mentoring Competence in Undergraduate Medical Education: A Quasi-Experimental Study - Ashraf, Rabia; Sadiq, Naushaba; Bashir, Noman; Zafar, Saira; Asif, Omaima; Mahmood, Asma (Journal of Postgraduate Medical Institute, 2025)
Objective: To assess mentors’ baseline competence prior to a mentor training workshop at Wah Medical College and to evaluate changes in overall mentoring proficiency and specific mentor skill domains following the intervention using a self-assessment tool. Methods: Faculties of Wah Medical College were involved in this quasi-experimental study and 35 numbers of faculty involved in mentoring were included. The intervention included two structured workshops separated over eight weeks, with the support of reflective and self – study phases. The Mentor Competency Assessment tool (MCA-21) was used pre and post the intervention. Results: The overall mentoring competence was found to significantly increase (p < 0.01) from statistical analysis. The most significant improvements were made in communication, fostering independence and enhancing professional development itself among the six mentoring domains. The findings from these outcomes confirm the value of structured mentor training in faculty development. Conclusion: Training based on experiential learning, in a structured manner, improves mentoring skill remarkably. To strengthen the quality of mentorship, and ultimately, student outcomes, institutions should be compelled to invest in such faculty development programs.